Mikroflora of the usual pumpkin seeds and gymnosperms - Melnyk , O.Y. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
The results of studies to determine the seeds of pathogens, the percentage of their development and the dominant species. And also shows the data taken from the literature.